Treatment and Mortality of Hemophagocytic Lymphohistiocytosis in Adult Critically Ill Patients: A Systematic Review With Pooled Analysis. Issue 11 (November 2020) - Knaak, Cornelia; Schuster, Friederike S.; Nyvlt, Peter; Spies, Claudia; Feinkohl, Insa; Beutel, Gernot; Schenk, Thomas; La Rosée, Paul; Janka, Gritta; Brunkhorst, Frank M.; Keh, Didier; Lachmann, Gunnar
Abstract : Objectives: Hemophagocytic lymphohistiocytosis is a cytokine release syndrome caused by uncontrolled immune activation resulting in multiple organ failure and death. In this systematic review, we aimed to analyze triggers, various treatment modalities, and mortality in critically ill adult hemophagocytic lymphohistiocytosis patients. Data Sources: MEDLINE database (PubMed) at October 20, 2019. Study Selection: Studies and case series of patients greater than or equal to 18 years old, of whom at least one had to be diagnosed with hemophagocytic lymphohistiocytosis and admitted to an ICU. Data Extraction: Source data of studies and case series were summarized and analyzed on an individual basis. Multivariable logistic regression analysis was performed adjusting for age, sex, and trigger groups. Each single treatment agent was entered as a dichotomous variable to determine treatments associated with survival, regardless if given alone or in combination. Data Synthesis: In total, 661 patients from 65 studies and case series were included. Overall mortality was 57.8%. Infections were the most frequent trigger (49.9%), followed by malignancies (28.0%), autoimmune diseases (12.1%), unknown triggers (9.4%), and drugs (0.6%). Treatment with IV immunoglobulins was associated with improved survival (odds ratio, 0.548; 95% CI, 0.337–0.891; p = 0.015), while treatment with cyclosporine was associated with increased risk of death (odds ratio, 7.571; 95% CI, 3.702–15.483; p < 0.001). Considering different trigger groups separately, same results occurred only for infection-triggered hemophagocytic lymphohistiocytosis. No information was available on disease severity and other confounding factors. Conclusions: Mortality of hemophagocytic lymphohistiocytosis in the ICU is high. Most common triggers were infections. Results of survival analyses may be biased by treatment indication and disease severity. Future studies prospectively investigating treatment tailored to critically ill hemophagocytic lymphohistiocytosis patients are highly warranted. Abstract : Supplemental Digital Content is available in the text.